Preparation and characterization of activated CMK-3 modified with vanadium applied in hydrogen storage - Juárez, Juliana; Gómez Costa, Marcos; Cussa, Jorgelina; Anunziata, Oscar (XXIII INTERNATIONAL MATERIALS RESEARCH CONGRESS, 2014)
The aim of this work is to synthesize a nanostructured Carbon CMK-3 modified with V in order to increase its capacity in hydrogen storage. The approach that we have followed includes synthesis of nanostructures with the experimental study of its adsorption capacity and storage properties. Ordered nanoporous carbon CMK-3 was synthesized via a two-step impregnation of the SBA-15 mesopores with a solution of sucrose using an incipient wetness method. The sucrose–silica composite was heated at 1173 K for 4 h under nitrogen flow. The silica template was dissolved with 5 wt% hydrofluoric acid in order to remove the silica. The template-free carbon product thus obtained was filtered, washed with deionized water and ethanol, and dried. [1] V-CMK-3 was prepared by wetness impregnation using VCl3 as source of Vanadium in order to increase the amount of hydrogen adsorbed. The sample of V-CMK-3 was treated under H2 flow two times at 1173 K. Porous carbon CMK-3 and the sample modified with V were characterized by XRD, FTIR, XPS, BET, TEM and SEM. These studies indicate that it was possible to obtain a CMK-3 replica successfully from SBA-15, using sucrose as a carbon precursor. [2] The surface areas are 1320 m2/g and 1050 m2/g for CMK-3 and V-CMK-3, respectively. While the nanomaterial area is significantly smaller with the incorporation of the metal, CMK-3`s characteristic structure is maintained after the metal is within the host, in agreement with the XRD studies. Measurements of hydrogen adsorption at cryogenic temperatures and low pressures were performed. The nanoparticles of V incorporated onto the nanostructured carbon CMK-3 showed higher hydrogen uptake at low and high pressures than CMK-3. (3.4 wt% and 2.2 wt% respectively of H2 sorption at 10 bar and 77 K).
Keywords: CMK-3; V-CMK-3; hydrogen